Molecular Docking, Synthesis and Evaluation for Antioxidant and Antibacterial Activity of New Oxazepane and Benzoxazepine Derivatives - Athra G. Sager; Jawad Kadhim Abaies; Zeena R. Katoof (مجلة بغداد للعلوم, 2024)
In the field of molecular simulations, molecular docking is a method that can determine the optimal and preferred orientation of a certain molecule related to another when they are coupled to create a stable complex. The strength of the association, or binding affinity, between two molecules can be predicted using knowledge of their preferred orientation.  In this study, a series of prepared compounds were evaluated for their binding modes, potential interactions, and target binding locations. Some derivatives 1,3-oxazepane, and 1,3-benzoxazepine were prepared from three Schiff bases compounds (1S-3S). The compounds (1S-3S) were reacted with succinic anhydride and phthalic anhydride to obtain derivatives of 1,3- oxazepane and 1,3-benzoxazepine (1B-3C). The characterization of prepared compounds was achieved by methods of elemental analysis, FT-IR, 1H, and 13C-NMR spectral analysis. The antibacterial activity of the compounds (1B-3C) was recorded against some isolated bacteria including gram-negative (Staphylococcus aureus), and gram-positive (E.coli) in parallel with Amoxicillin as a regular drug. Compounds (1B-3C) exhibited good values as antibacterial spreading from middling to perfect against the bacteria strains. Moreover, the antioxidant activity of the synthesized compounds (1B-3C) was evaluated using 2,2-diphenyl-1-picrylhydrazyl. The results showed that compounds have the highest values as radical scavenging.